Differential Gene Expression in Differentiated Human Neuroblastoma SH-SY5Y Cells in Response to a Cocktail of Monoamine Oxidase Inhibitors - Niraula P; Page RA; Palmer BR; Truman P (MDPI (Basel, Switzerland), 2026)
Differentiated human neuroblastoma (SH-SY5Y) cells were exposed to either 0.2 μM nicotine, a tobacco smoke preparation (TPM) diluted to the same nicotine concentration, or a cocktail of seven tobacco smoke monoamine oxidase inhibitors (MAOIs) at the concentrations measured in the TPM. Treatment occurred for 3 days, such that the cellular monoamine oxidase (MAO) concentration was reduced by approximately 50% in both the TPM and MAOI cocktail exposure groups. Changes in MAO gene expression after exposure to the different treatments were determined using qPCR, and the effect of these exposure treatments on global gene expression was also examined using mRNA sequencing. No change in MAOA and MAOB gene expression levels was observed, after any treatment, either using qPCR or mRNA sequencing. The MAOI versus control treatment comparison revealed that four genes were >2-fold down-regulated (ZNF727, RP11-310E22.4, CRYM, SEMA3F), and 19 genes were up-regulated after 3 days’ exposure to the MAOI cocktail. Many of these differentially expressed genes were linked with disease conditions related to smoking and addiction. Exposure to nicotine and TPM each resulted in up- and down-regulation of different sets of genes. The results indicate that changes in MAO gene expression are unlikely to be responsible for the changes in MAO activity. The association between genes whose expression changes with tobacco MAO treatment and smoking-related diseases and addiction suggests the central role that MAO inhibition may play in mediating the effects of smoking on smokers.
Keywords: monoamine oxidase inhibitors; tobacco dependence; nicotine; tobacco particulate matter; global gene expression; qPCR